Examining Health and Relationship Beliefs in Family Discourses About Purity Pledges: Gender, Faith Values, and the Communicative Constitution of Reality. Issue 1 (1st January 2017) - Manning, Jimmie
Abstract : This research draws from multiadic interview data with 13 purity-pledge families to explore parental roles in sex education. The use of values coding reveals that participants present their beliefs in three ways: as research-oriented facts about sex and sexuality; as common-sense logic; and as informed by personal lived experience. These beliefs are both health- and relationship-oriented. Implications include how knowledge is selected and applied by parents in family talk about sex, gendered ways parents share sexual history, and problematic aspects of purity pledge talks. The study also adds to a larger cultural discourse regarding faith and the politics of science.